Answer :


Formula used:



where,



Here, a = 0 and b = 1


Therefore,




Let,



Here, f(x) = 3x2 + 5x and a = 0




Now, by putting x = 0 in f(x) we get,


f(0) = 3(0)2 + 5(0) = 0 + 0 = 0


f(h)


= 3(h)2 + 5(h)


= 3h2 + 5h


Similarly, f(2h)


= 3(2h)2 + 5(2h)


= 3h2(2)2 + 5h(2)



Now take 3h2 and 5h common in remaining series





Put,



Since,
















Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2